A Walk on the Wild Side: 2024 Cool-Season Forage Recommendations for Wildlife Food Plots in North Florida - M. Wallau; A. R. Blount; J. M. Campos-Krauer; M. A. Lashley; E. Rios; J. M. B. Vendramini; J. C. B. Dubeux; Md. A. Babar; C. L. Mackowiak; C. H. L. de Souza; K. H. Quesenberry (EDIS)
The list of cool-season forage recommendations for wildlife in this publication includes varieties that have been tested and are known to perform well in Florida.